IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURAL PARAGRAPH THROUGH DEMONSTRATION METHOD - Linda; Lince Sihombing (Universitas Negeri Medan, 2014)
This study concerns with improving grade VIII students’ achievement in writingprocedural Paragraph through demonstration method. This research wasconducted by using classroom action research. The subject of the study was gradeVIII students of SMP N 2 Babalan which consisted of 35 students. Theinstruments for collecting data were primary data (writing test) and secondarydata (interview sheet, observation sheet and questionnaire sheet). Based onwriting scores, students’ score kept improving in every evaluation. In the test I themean was 64,91, in the test II the mean was 74,57 . Based on interview, observation,and questionnaire sheet, it was found that teaching-learning process ran well.Students were active, creative to give their idea, enthusiastic, and interested inwriting. The finding of the research showed that applying demonstration methodsignificantly improved students’ writing achievement.